Numerical study of n-pentane separation using adsorption column - Adriano da Silva; Viviana Cocco Mariani; Antônio Augusto Ulson de Souza; Selene Maria de Arruda Guelli Ulson Souza (Brazilian Archives of Biology and Technology, 2005)
This work simulated numerically the n-pentane separation of a mixture of iso-pentane, n-pentane and nitrogen, using an adsorption column with zeolite 5A. The mathematical model equations of the mass and heat transfer in the adsorption column are presented, as well as the boundary and initials conditions, beyond some hypotheses and considerations. The Volume Finite Method was used in the discretization of the equations to get the system of algebraic equations and posterior development of the computational algorithm. The numerical results using the Differencing Central (CDS) and Upwind (UDS) interpolations were compared with experimental results found in the literature. The influence of the partial pressure in the adsorption column performance was also analyzed. Neste trabalho é simulada numericamente a separação de n-pentano de uma mistura contendo iso-pentano, n-pentano em uma corrente de nitrogênio (inerte), em uma coluna de adsorção de leito fixo empacotada com zeólita 5A. São apresentadas as equações do modelo matemático da transferência de calor e massa na coluna de adsorção, bem como suas condições de contorno e iniciais, além de algumas hipóteses e considerações. Utiliza-se o Método de Volumes Finitos para discretizar as equações e obter um sistema de equações algébricas aproximadas e posterior desenvolvimento do algoritmo computacional. Os resultados numéricos utilizando as interpolações Diferença Central (CDS) e Upwind (UDS) são comparados com resultados experimentais obtidos na separação do n-pentano encontrados na literatura. A influência da pressão parcial no desempenho da coluna de adsorção de leito fixo também é analisada.